PEMBERITAAN KABAR BAIK MELALUI RADIO KHARISMA BANDUNG - Yanto Paulus Hermanto (Jurnal PKM Setiadharma, 2021)
The call to preach the good news is an urgent matter so that mankind's biggest problem, namely sin, can be resolved. The Bible begins by describing the tragic human condition, a situation only the Bible can answer. Through the gospel, human sins can be resolved and humans can return to peace with God. The preaching of the gospel must be done because it is God's desire that all sinful humans can be saved from eternal punishment. STT Kharisma to meet these goals in collaboration with radio kharisma. And committed to preaching the good news every week to Kharisma 828 AM radio listeners. The method used in delivering this good news is by means of lectures, and interactive discussions both with charisma radio listeners and with other sources. Of course the target is so that charismatic radio listeners can grow spiritually. The procedure for preaching the good news is planned in such a way as to be structured and systematic so that it is easy to understand and understand. And finally the message recipients (charisma radio listeners) can get to know the Lord Jesus and grow spiritually.